1985
DOI: 10.1111/j.1432-1033.1985.tb09095.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the GTPase domain of archaebacterial ribosomes

Abstract: Ribosomes from the methanogens Methanococcus vunnielii and Methanobacterium jormicicum catalyse uncoupled hydrolysis of GTP in the presence of factor EF-2 from rat liver (but not factor EF-G from Escherichiu coli). In this assay, and in poly(U)-dependent protein synthesis, they were sensitive to thiostrepton. In contrast, ribosomes from Sulfolohus solfataricus did not respond to factor EF-2 (or factor EF-G) but possessed endogenous GTPase activity, which was also sensitive to thiostrepton. Ribosomes from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
1
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 45 publications
0
62
1
1
Order By: Relevance
“…Fig. 5A) is involved in EF-G-dependent functions (5)(6)(7)(8)(9)(10)(11). Thiostrepton, an antibiotic that inhibits binding of EF-G to ribosomes (5), binds to a 23S rRNA fragment that has A1067 (26); in addition, methylation of the 2Ј-hydroxyl of A1067 confers resistance to thiostrepton in strains of Streptomyces aureus (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 5A) is involved in EF-G-dependent functions (5)(6)(7)(8)(9)(10)(11). Thiostrepton, an antibiotic that inhibits binding of EF-G to ribosomes (5), binds to a 23S rRNA fragment that has A1067 (26); in addition, methylation of the 2Ј-hydroxyl of A1067 confers resistance to thiostrepton in strains of Streptomyces aureus (6).…”
Section: Resultsmentioning
confidence: 99%
“…There are threedimensional structures of EF-G alone (3) and in a complex with GDP (4) from x-ray crystallography; however, little is known of the chemistry of the binding of the factor to ribosomes. There is evidence for the interaction of EF-G with two separate sites in Escherichia coli 23S rRNA: with the thiostrepton region (5)(6)(7)(8)(9)(10)(11) and with the sarcin͞ricin (S͞R) domain (11,12).…”
mentioning
confidence: 99%
“…This is comparable with the fact that rat L12 and anti-28 S recognize a similar tertiary structure of the eukaryotic GTPase domain. The E. coli-L8 complex (a counterpart of the rat P complex) binds to the GTPase domain of 23 S rRNA through L10 moiety (Pettersson et al, 1976;Pettersson, 1979;Beauclerk et al, 1984) and protects mainly the internal loop region comprising residues 1044 -1050 and 1109 -1111 against chemical reagents and nuclease (Egebjerg et al, 1990;Rosendahl and Douthwaite, 1993). This loop region is highly conserved; 7 of 10 bases are preserved between E. coli and rat.…”
Section: Conserved Protein Binding Features Of the Gtpase Domain-mentioning
confidence: 99%
“…This RNA region has been identified as a site of interaction with elongation factor G (Sköld, 1983;Moazed et al, 1988) and with the antibiotic thiostrepton, an inhibitor of elongation factor-dependent processes in protein synthesis (Thompson et al, 1982;Egebjerg et al, 1989). Ribosomal protein L11 and the acidic protein complex L10(L12) 4 cooperatively bind to this RNA domain (Dijk et al, 1979;Beauclerk et al, 1984) and construct a functional site of the 50 S subunit. L11 may participate in induction of a functionally important RNA conformation (Xing and Draper, 1995).…”
mentioning
confidence: 99%
“…With this method, we demonstrated that a human autoantibody specifically binds to an RNA region corresponding to residues 1944-2002 of human 28S rRNA (or residues 1767 1825 of mouse 28S rRNA) [9]. This region is highly conserved and termed the GTPase domain [9,16]. To address questions of the frequency of such autoantibody in patients with SLE and of whether 28S rRNA has any other autoimmune targets, sera from 120 patients (90 patients with SLE, 10 with rheumatoid arthritis, five with scleroderma, four with polymyositis and 11 with miscellaneous autoimmune diseases) were tested by the RNase protection assay.…”
Section: Resultsmentioning
confidence: 99%